UPAYA BADAN KEUANGAN DAERAH DALAM MENINGKATKAN PENERIMAAN PAJAK BUMI DAN BANGUNAN PEDESAAN-PERKOTAAN/PBB-P2 DI KABUPATEN LIMA PULUH KOTA TAHUN 2020-2021 - Rahmadani, Afiva Novitri; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to find out how regional financial institutions' efforts to increase the revenue of the Earth and Rural and Urban Buildings/PBB-P2 Tax in the City of Lima West Sumatra Province in 2020-2021. The research problem is the efforts of the Regional Finance Agency of Lima-Kota Regency that have not been maximized in increasing the revenue of the Earth Tax and Rural-Rural Buildings. This study is a descriptive study with a qualitative approach. Data types are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data supporting or strengthening primary data. Data collection techniques are conducted by interviews and documentation. The results of this study show that the implementation of efforts carried out by the Regional Finance Agency of kabupaten Lima Puluh Kota in 2020-2021 has been carried out quite well using the Intensification and Extensions system. However, there are several inhibitory factors that cause a slight slowdown in the Regional Finance Agency of kabupaten Lima Puluh kota in maximizing its efforts to increase the revenue of the Earth Tax and Rural-Rural Buildings. The two factors that hinder the efforts of the Regional Finance Agency of kabupaten Lima Puluh kota in increasing the awareness of taxpayers are internal inhibition factors and external inhibition factors. Kata Kunci: Efforts, Receipts, Local Taxes, Earth and Building Taxes